Türkiye and the Belt and Road Initiative - Ataçay, M. Nergis (IGI Global, 2025)
The Belt and Road Initiative (BRI), which is an extensive transportation and infrastructure project, connecting Asia, Africa, and Europe is also seen as one of the important tools of South-South cooperation. Türkiye as one of the important members of the BRI has had several expectations, mainly improving Sino-Turkish relations through increasing Chinese investments in Türkiye and reducing the pressure of the trade deficit of Türkiye given to China. In addition, it was anticipated that the BRI would have improved trade and investment relations of Türkiye with the other members, so that the initiative would also play a role in Türkiye's rapprochement to the rising Global South. On the other hand, Chinese investments in Türkiye have been insufficient since its inclusion in the BRI in 2015, and the two countries would mutually put efforts to realize the potential benefits of the BRI.